2013
DOI: 10.3390/ijms140917511
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Molecular Changes of the Bladder in Rats with Crushing Injury of Nerve Bundles from Major Pelvic Ganglion to the Bladder: Role of RhoA/Rho Kinase Pathway

Abstract: Voiding dysfunction is a common complication after radical pelvic surgery. To reduce this complication, nerve-sparing radical pelvic surgery was introduced. However, several patients experienced voiding difficulty despite nerve-sparing radical pelvic surgery. Thus, we investigated the functional and molecular changes of the bladder in rats, which demonstrated voiding dysfunction induced by nerve damage during nerve-sparing radical pelvic surgery. Male rats were used and assigned to normal, sham-operated, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Contraction at later time points successively increased to closely approximate sham contraction by 30 days post-nerve crush. In male rats, decreased detrusor contraction to both low and high frequency EFS was evident 1, 2 and 4 weeks post-injury [24]. These findings suggest a decline in available bladder cholinergic nerve activation following BPNI which is also supported by the decrease in markers specific to cholinergic nerve terminals 7–30 days following BPNI.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Contraction at later time points successively increased to closely approximate sham contraction by 30 days post-nerve crush. In male rats, decreased detrusor contraction to both low and high frequency EFS was evident 1, 2 and 4 weeks post-injury [24]. These findings suggest a decline in available bladder cholinergic nerve activation following BPNI which is also supported by the decrease in markers specific to cholinergic nerve terminals 7–30 days following BPNI.…”
Section: Discussionmentioning
confidence: 95%
“…A comparable switch following BPNI may explain increased carbachol contractile response during periods of decreased M3 receptor expression. In contrast, a male rat model of cavernous nerve crush injury found increased M2 and no change in M3 protein expression at 1, 2 and 4 weeks post-crush [24]. Further studies are required to elucidate the role of M2 versus M3 receptor following BPNI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that bladder weight increased after PNT but improved after hAFSCs transplantation. Bilateral pelvic nerve crush could cause detrusor muscle hypertrophy and increase collagen deposition 12,13 , and bilateral PNT caused bladder wall muscle hyperplasia and hypertrophy with increased bladder weight in rats 14 . However, Kwon et al 15 reported that unilateral PNT caused no change of bladder weight in rats treated with muscle-derived stem cells and sham operation and also no change in normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several published studies reported as a UAB model by using pelvic nerve crash- or cryoinjury (unilaterally or bilaterally) [ 92 93 94 95 96 ], in which detrusor contractility was remarkably impaired. In case of bilateral pelvic nerve injury by complete resection, the animals showed severe nervous dysfunctions, which were resemble to the situation with SCI [ 95 ].…”
Section: Animal Models For Underactive Bladdermentioning
confidence: 99%